Analysis and synthesis of networked control systems - Xia, Yuanqing; Fu, Mengyin; Liu, G. P. (Guo Ping) 1962-.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
Analysis and Synthesis of Networked Control Systems focuses on essential aspects of this field, including quantization over networks, data fusion over networks, predictive control over networks and fault detection over networks. The networked control systems have led to a complete new range of real-world applications. In recent years, the techniques of Internet of Things are developed rapidly, the research of networked control systems plays a key role in Internet of Things. The book is self-contained, providing sufficient mathematical foundations for understanding the contents of each chapter. It will be of significant interest to scientists and engineers engaged in the field of Networked Control Systems.   Dr. Yuanqing Xia, a professor at Beijing Institute of Technology, has been working on control theory and its applications for over ten years.
Part I Quantization over networks -- Part II Data fusion over networks -- Part III Predictive control over networks -- Part IV Fault detection over networks.
Electronic reproduction.
Keywords: Automatic control; System theory; Electronic books